Aloe-Emodin Suppresses Oxidative Stress and Inflammation via a PI3K-Dependent Mechanism in a Murine Model of Sepsis. (8th August 2022) - Gao, Huijie; Ren, Yan; Liu, Chao
Abstract : Background . This study was designed to assess the impact of aloe-emodin (AE) on oxidative stress and inflammation in a murine model of LPS-induced sepsis. In addition, the mechanistic basis for anti-inflammatory and antioxidant activity was assessed. Methods . Male ICR mice received an intraperitoneal injection of LPS (10 mg/kg), and the preventive properties of AE (80 or 150 mg/kg) on these mice were assessed by monitoring spleen index, and levels of inflammatory and oxidative stress-related factors. Peripheral blood TNF- α and IL-6 levels were assessed via ELISA kits, while changes in hepatic SOD and GSH-Px levels were assessed using appropriate biochemical kits. Splenic PI3K, AKT, and mTOR levels were assessed via qPCR and western blotting. Results . Relative to animals in the LPS model group, those in the AE treatment groups exhibited reduced spleen index, decreased inflammatory cytokine levels, and improved SOD and GSH-Px activity in liver tissues. Splenic PI3K, Akt, and mTOR levels were also reduced in response to AE treatment. Conclusions . These findings indicated that AE can alleviate sepsis-related tissue damage, inflammation, and oxidative stress, at least in part by suppressing the PI3K/Akt/mTOR signaling pathway. These results offer a clinical basis for the use of AE to treat sepsis and associated diseases.